"Industry 4.0: Benefit From Opportunities. Today. Tomorrow.": Interview with Teka General Manager Erwin Telöken. Issue 5 (7th November 2017) - Unknown
Abstract: Getting not only industrial processes ready for Industry 4.0 but also peripherals in the infrastructure, is obtaining increased attention – especially at the major industry fairs. As Teka was presenting its new Airtracker Mini (cf. p. 36) – which will also be featured at the Blechexpo – we took the opportunity to visit the Teka booth at the Schweissen & Schneiden in September.